2011
DOI: 10.1557/jmr.2011.207
|View full text |Cite
|
Sign up to set email alerts
|

Facet-selective growth and optical properties of CdTe/CdSe tetrapod-shaped nanocrystal heterostructures

Abstract: Selective CdSe tip growth on CdTe tetrapod-shaped colloidal seeds has been achieved for a Cd: surfactant molar ratio of 1:2, where surfactant is oleic acid. The average length of tetrapod arms increased from 12 to 21 nm while arm width remained constant of 3 nm. Formation of CdSe tips shifts the excitonic absorption maximum to the near-infrared region and the appearance of low-intensity absorption feature corresponding to a charge-transfer band. At the same time, luminescence band splits into a narrow (about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…This ultimately results in a significant number of side-linked rods, even surpassing the number of tip-linked rods at an Ag + concentration of 1.6 mM. Such structures are difficult to synthesize via the heterogeneous nucleation and growth of CdSe on CdTe TPs, which tends to localize the CdSe domains at the tetrapod tips . On the other hand, the same high concentration of Ag + facilitates cation exchange exclusively at the tips of the CdSe NRs, which are generally less prone to Ag + exchange than CdTe, as explained before.…”
Section: Resultsmentioning
confidence: 98%
“…This ultimately results in a significant number of side-linked rods, even surpassing the number of tip-linked rods at an Ag + concentration of 1.6 mM. Such structures are difficult to synthesize via the heterogeneous nucleation and growth of CdSe on CdTe TPs, which tends to localize the CdSe domains at the tetrapod tips . On the other hand, the same high concentration of Ag + facilitates cation exchange exclusively at the tips of the CdSe NRs, which are generally less prone to Ag + exchange than CdTe, as explained before.…”
Section: Resultsmentioning
confidence: 98%
“…We first tested the effect of excess OA, which could impact the gelation behavior due to interactions with the Cd oleate complex in solution. For example, QD synthesis reactions are often performed with varying amounts of OA to control the resulting nanocrystal product, where higher OA concentrations are used to increase the solubility of Cd-precursors and reactive monomers. , Molar equivalents of OA (between 1 and 20× excess) were added to Cd oleate in toluene at a constant total volume. We found that excess OA solubilizes Cd oleate in toluene rather than forming a stable gel.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrapod-shaped CdTe/CdSe nanocrystal heterostructures were synthesized following the procedure described in ref . Nanotetrapods consist of the CdTe tetrapod core and arms (the average length of the CdTe tetrapod arms was about 12 ± 1 nm, and the average width was about 3 nm) with the CdSe extensions (the average length of the CdSe tips was about 11 ± 1 nm, and the average width was about 3 nm) grown selectively at the ends of each arm.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to the other types of semiconductor nanocrystals, the optical and electronic properties of nanotetrapods are determined by the properties of excitons: electron–hole pairs bound by the Coulomb interaction, which are formed when light interacts with the system. Most of the results corresponding to the electronic and optical properties of tetrapod shaped type II heterostructured nanocrystals were obtained in the regime of nonstationary photon exciton excitation by means of ultrashort laser pulses. ,, Features of exciton dynamics in tetrapod shaped type II heterostructured nanocrystals were studied under stationary single exciton excitation of the main electron–hole transition in one of the domains of the nanotetrapods, while the processes of excitation and relaxation of charge carriers under pulsed optical excitation with energy significantly higher than the excitation energy of the main exciton transitions are still not well understood and investigated. Moreover, the problem of charge carrier spatial localization in nanotetrapods is still not well understood.…”
Section: Introductionmentioning
confidence: 99%